2013
DOI: 10.1002/chem.201303026
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Modulation in Tribranched Switchable [4]Rotaxanes

Abstract: Two novel tribranched [4]rotaxanes with a 1,3,5-triphenylene core and three rotaxane arms have been designed, synthesized, and characterized by (1)H and (13)C NMR spectroscopies and HR-ESI mass spectrometry. [4]Rotaxanes 1 and 2 each possess the same three-armed skeleton. Each arm incorporates two distinguishable binding sites for a dibenzo[24]crown-8 ring, namely a dibenzylammonium site and an N-methyltriazolium site, and is terminated by a 4-morpholino-naphthalimide fluorophore as a stopper. [4]Rotaxane 1 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…First, we analyzed the 1 H NMR spectrum of [3]rotaxane 2‐H (Figure 1 a). Compared with our previously synthesized rotaxanes,9b, d, 12c, 14b the 1 H NMR spectrum of [3]rotaxane 2‐H revealed that the DB24C8 macrocycles predominately resided on the DBA recognition sites in rotaxane 2‐H . What’s more, compared with the 1 H NMR spectrum of rotaxane 2‐H (Figure 1 a), there was a new peak of H15 at δ =4.33 ppm in the rotaxane 1‐H (Figure 1 b) because of the methylation of the triazole unit.…”
Section: Methodsmentioning
confidence: 67%
“…First, we analyzed the 1 H NMR spectrum of [3]rotaxane 2‐H (Figure 1 a). Compared with our previously synthesized rotaxanes,9b, d, 12c, 14b the 1 H NMR spectrum of [3]rotaxane 2‐H revealed that the DB24C8 macrocycles predominately resided on the DBA recognition sites in rotaxane 2‐H . What’s more, compared with the 1 H NMR spectrum of rotaxane 2‐H (Figure 1 a), there was a new peak of H15 at δ =4.33 ppm in the rotaxane 1‐H (Figure 1 b) because of the methylation of the triazole unit.…”
Section: Methodsmentioning
confidence: 67%
“…4). 45 Another tetrapodal [5]rotaxane 18 was reported by Qu using the same di-ferrocene-linked DB24C8 with the simple 3,5-dimethoxyl stopper while the core was the Zn(II) porphyrin (Fig. 4).…”
Section: Type II Rotaxane Dendrimersmentioning
confidence: 95%
“…With further research for switchable rotaxane‐containing fluorophores, ferrocene‐modified rotaxane attracted more and more attention 10f. g, km A pyrene/ferrocene‐based [2]rotaxane with a three‐level luminescent response was reported by Mateo‐Alonso et al.,10f and a ferrocene‐functionalized molecular shuttle was constructed by Qu and co‐workers, in which the fluorescence of the rotaxane can be reduced or enhanced alternately by an adjustable photoinduced electron transfer (PET) process occurring between two ferrocene (Fc) units in the macrocycle and two fluorescent stoppers 10l. However, it is still a challenge to construct systems in which the shuttling motion of the macrocycle is accompanied with different fluorescence responses, and surely this system would pave the way for constructing more complicated and delicate multilevel molecular switches with optical signals.…”
Section: Methodsmentioning
confidence: 99%